Catalytic synthesis of glycol dicarbonate from glycol and dimethyl carbonate by transesterification. Issue 5 (May 2019) - Chen, Ruiyang; Chen, Tong; Hu, Xiaojia; Fan, Youkun; Wang, Gongying
Glycol dicarbonate is successfully synthesized via transesterification of glycol with dimethyl carbonate. A catalyst screening is performed by studying the effect of acidity and alkalinity on the catalytic performance. The results indicate that compared with acidic catalysts, high conversions and yields are obtained with basic catalysts. Ca(OH)2, with medium-strength alkalinity, exhibits excellent catalytic activity with glycol dicarbonate yields of 95%-99% when using a fractionation reaction system.